Thoracic Endovascular Repair for Acute Traumatic Transection of the Descending Thoracic Aorta and Postendovascular Remodeling Change - Kim, Joung Taek; Kim, Young Sam; Yoon, Yong Han; Shin, Helen Ki; Park, Keun Myoung; Baek, Wan Ki (The Thoracic and Cardiovascular Surgeon, 2018)
Background The recently developed thoracic endovascular repair (TEVAR) technique seems to offer a good alternative for treating acute traumatic transection of the thoracic aorta (TTA). We reviewed our experience of TEVAR in cases of acute traumatic transection and analyzed the subsequent remodeling changes.Methods The medical records of 17 patients who underwent TEVAR for TTA were reviewed. The trauma mechanisms, anatomical characteristics of the transected aortas, technical details of TEVAR, and postprocedural results were reviewed.Results The overall mean injury severity score was 53 ± 12. On three-dimensional computed tomography (CT), the mean distance of transection from the left subclavian artery was 14 ± 9 (0–31) mm. Fifteen patients presented an aortic pseudoaneurysm and two patients had impending rupture. TEVAR was performed emergently under general endotracheal induction. Technical success was achieved and complete pseudoaneurysm sealing was confirmed with aortography in all 17 patients. Two patients (12%) died of hypovolemic shock and hyperkalemia; however, no late death or stent-related complication occurred during the 45 ± 32 (6–102) months of follow-up. During a mean CT follow-up of 35 months, the mean aortic diameter increased by 2 (0–5) mm and pseudoaneurysm lesions completely disappeared in all patients.Conclusions TEVAR resulted in good early survival in patients with TTA. No late or stent graft-related event was encountered up to a maximum of 9 years after surgery. We recommend that patients with grade III or higher TTA should undergo emergency surgery. Moreover, we consider that long-term follow-up and blood pressure management are essential when the proximal aortic diameter is found to increase slightly after TEVAR on follow-up CT.
Keywords: aorta; trauma; stent graft